A Case Study on Pellet Gun Injury - Zunga, Pervaiz Majeed; Majid, Obaid (Highlights on Medicine and Medical Research Vol. 13, 2021)
Pellet gun inury can cause grevious and serious injuries especially of soft tissues and sensitive organs like eyes. Pellet gun used by law enforcement agencies have the potential to cause grevious or life threatening injuries as metallic projectiles fired at high speeds from pellet gun have potential to damage strongest structure likebone. The present case was observed in a series of patients who was hospitalized with pellet gun injury in the different consequences.